Influence of Combined Mechanical Processes on Tribological Properties of Tool Steels Vanadis 8 and Vancron 40 With a Similar Hardness - Toboła, Daniel; Łętocha, Aneta (Frontiers in Mechanical Engineering, 2021)
For components like cold working tools, exposed to wear, for which the main desirable properties are suitable hardness combined with high wear resistance aspects of surface integrity are an important factors. Mechanical treatments are the most common improvement procedures in this case. Several types of surface treatments, such as grinding, hard turning, and hard turning with slide burnishing using different forces were performed. Vancron 40 and Vanadis 8 tool steels, with a different chemical composition were investigated. Different types and amounts of carbides after heat treatment were determined for both materials. Heat treatment was carried out in vacuum furnaces with gas quenching to hardness of 64±1 HRC (Vancron) and 65±1 HRC (Vanadis). 3D topography, optical and scanning electron microscopy, X-ray diffraction and finally ball-on-disc tribological tests against Al2O3 and 100Cr6 balls as counterparts provided values about wear and friction. For both investigated steels, the lowest values of dynamic frictions and wear rates were achieved after sequential process of hard turning with slide burnishing, applying a burnishing force of 180 N. Increase of wear resistance (against Al2O3 counterbodies) achieved after hard turning plus burnishing in comparison to grinding exceeds 50% and 60%, respectively for Vanadis 8 and Vancron 40 steels.